Potential Therapeutic Drugs for Parkinson’s Disease Based on Data Mining and Bioinformatics Analysis - Chuan Xu; Jiajun Chen; Xia Xu; Yingyu Zhang; Jia Li (Parkinson's Disease)
The objective is to search potential therapeutic drugs for Parkinson’s disease based on data mining and bioinformatics analysis and providing new ideas for research studies on “new application of conventional drugs.” Method differential gene candidates were obtained based on data mining of genes of PD brain tissue, original gene data analysis, differential gene crossover, pathway enrichment analysis, and protein interaction, and potential therapeutic drugs for Parkinson’s disease were obtained through drug-gene relationship. Result. 250 common differential genes were obtained from 3 research studies, and 31 differential gene candidates were obtained through gene enrichment analysis and protein interaction. 10 drugs such as metformin hydrochloride were directly or indirectly correlated to differential gene candidates. Conclusion. Potential therapeutic drugs that may be used for prevention and treatment of Parkinson’s disease were discovered through data mining and bioinformatics analysis, which provided new ideas for research and development of drugs. Results showed that metformin hydrochloride and other drugs had certain therapeutical effect on Parkinson’s disease, and melbine (DMBG) can be used for treatment of Parkinson’s disease and type 2 diabetes patients.